1994
DOI: 10.1152/jappl.1994.76.3.1123
|View full text |Cite
|
Sign up to set email alerts
|

Differential reflex control of forearm and calf resistance vessels by chemosensitive cardiac afferent activation

Abstract: The aim of this study was to determine whether chemosensitive ventricular afferent activation in humans evokes a diffuse pattern of reflex vasodilation involving the skeletal muscle circulation of all the extremities or a highly specified pattern of vasodilation that is limited to the rather small vascular bed of the forearm. In 10 patients with innervated ventricles and 7 patients with denervated ventricles resulting from heart transplantation, we performed simultaneous plethysmographic recordings of blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Differences in sympathetic vasoconstrictor outflow to the arm and the leg in response to intraarterial adenosine might account for the dissociation between TBS, which increased, and NAR in the contralateral noninfused forearm, which did not. Similar discordance has been observed during mental stress (33), or on stimulation of chemosensitive cardiac afferents (34). However, Wallin and colleagues demonstrated that circulatory arrest, after handgrip, increases muscle sympathetic traffic in both the opposite radial, and in the peroneal nerve (35), leading us to anticipate an increase in NAR in the contralateral arm in these experiments.…”
Section: Discussionsupporting
confidence: 61%
“…Differences in sympathetic vasoconstrictor outflow to the arm and the leg in response to intraarterial adenosine might account for the dissociation between TBS, which increased, and NAR in the contralateral noninfused forearm, which did not. Similar discordance has been observed during mental stress (33), or on stimulation of chemosensitive cardiac afferents (34). However, Wallin and colleagues demonstrated that circulatory arrest, after handgrip, increases muscle sympathetic traffic in both the opposite radial, and in the peroneal nerve (35), leading us to anticipate an increase in NAR in the contralateral arm in these experiments.…”
Section: Discussionsupporting
confidence: 61%
“…Several stimuli have been reported to produce heterogeneous regional vascular responses in skeletal muscle. For example, orthostatic stress (5,6), cold stress (13), and ventricular chemoreceptor activation (14) may elicit differential responses. Despite lower norepinephrine spillover from legs compared with arms (13,16), neural traffic to arm and leg skeletal muscle during orthostatic stress appears to be relatively uniform (22,29).…”
Section: Perspectivesmentioning
confidence: 99%